The impact of product returns on price and delivery time competition in online retailing. (November 2018) - Zhao, Sisi; Wu, Feng; Jia, Tao; Shu, Lei
Highlights: We study the price and promised delivery lead time competition between two e-tailers. We construct the product returns due to late/early delivery inaccuracy into mathematic model. We prove that the Nash Equilibrium is unique in two cases. The impact of asymmetry in return parameters on the equilibrium is examined. Abstract: This paper studies price and promised delivery lead time (PDL) competition between two e-tailers in the context of e-commerce. Product returns are considered, which are affected by late and early delivery inaccuracies, i.e., the delay and early arrival of random actual delivery time relative to PDL. The goal is to examine whether the Nash Equilibrium exists in the competition, and to explore the impact of product returns on equilibrium solutions. We consider two cases where the sensitivities of the return rate to late delivery inaccuracy and early delivery inaccuracy are symmetric/asymmetric. The results suggest that (1) firms with lower basic return rates or lower return rate sensitivities, always quote higher prices and shorter PDLs; (2) it is not always profitable for firms whose competitors' return parameters increase.